Busca360: A Search Application in the Context of Top-Side Asset Integrity Management in the Oil & Gas Industry - T. Izquierdo, Yenier; Lemos, Melissa; Oliveira, Cleber; Novelli, Bruno; M. García, Grettel; Coelho, Gustavo; Feijó, Lucas; Coutinho, Bruno; Santana, Tiago; Souza Garcia, Robinson Luiz; Casanova, Marco Antonio (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2024: Anais do XXXIX Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2024.240793, 2024)
Oil and gas industry applications often require querying data of various types and integrating the query results. Data range from structured tables stored in databases to documents and images organized in digital libraries. The users typically have technical training but are not necessarily versed in Information Technology, meaning the data processing tasks may burden them significantly. This article introduces a multimodal search application, called Busca360, designed to alleviate this burden and discusses the main challenges that emerged during the research, implementation, and user experience. The application uses structured data in the context of asset integrity management and 360º images of equipment and installation locations. Finally, this article concludes with real-world use cases that show how the proposed multimodal search application helps perform planning and maintenance tasks.